Assessing the Impact of Hydraulic Retention Time and Sawdust on the Elimination of Pb and Co from Oily Wastewater via Vertical-Flow Constructed Wetlands (VFCWs) with Phragmites Australis Cultivation - Hayede Nafasi; Azadeh Hemmati; Fatemeh Aghamohammadi; Ali Afrous (Iranian Journal of Chemical Engineering)
Constructed wetlands have been increasingly used as an effective method for removing heavy metals from wastewater. This study aimed to investigate the combined effect of sawdust and Hydraulic Retention Time (HRT) on the performance of vertical-flow constructed wetlands cultivated with Phragmites Australis to remove Pb and Co from oily wastewater. To this end, nine barrels were used to construct the wetlands, which were filled with coarse gravel, polluted soil, and varying percentages of sawdust (0%, 20%, and 40%). Phragmites Australis cuttings were then cultured inside the barrels and irrigated with heavy metal-contaminated oily wastewater for three different hydraulic retention times (5, 10, and 15 days). After the vegetation period, plant, soil, and wastewater samples were collected and analyzed for Co and Pb concentrations, from which transfer factor (TF), bioconcentration factor (BCF), and removal efficiency (%) were derived. Results showed that while both Pb and Co removal efficiencies were affected by HRT and sawdust, the removal efficiency of Pb (36.66%) was higher than that of Co (30.83%). TF was less than one and was not affected by HRT and sawdust, but the effect of HRT and sawdust on increasing BCF was significant. However, Phragmites Australis demonstrated suboptimal performance in the uptake and transfer of metals from the root to stem.